The role of ubiquitin ligases in regulating immune cell functions - Marty, Saci-Elodie; Yip, Linda; Wang, Fangyuan; Kumar, Manoj; Fathman, C. Garrison (Frontiers in Immunology, 2025)
Regulatory T cells (Tregs) play a central role in immune homeostasis and the preservation of immunological self-tolerance. Treg activity depends on prolonged IL-2 receptor (IL-2R) signaling, and impairment or loss of this function has been linked to the development of autoimmune diseases. This review evaluates the hypothesis that disrupted IL-2R signaling, due to enhanced desensitization, impairs Treg suppressive function and contributes to autoimmunity. In mice and humans, desensitization of IL-2R signaling by the cullin-RING ligase 5 (CRL5) complex leads to reduced persistence of phosphorylated JAK1 (pJAK1) and its downstream effector pSTAT5, a transcription factor critical for Treg function. Activation of CRL5 requires neddylation—a post-translational modification in which the ubiquitin-like NEDD8 is conjugated to lysine 724 on cullin-5 (CUL5), the scaffold protein of CRL5. Neddylation permits untethering of the RING-box protein RBX, enabling E2 enzyme-mediated ubiquitination and proteasomal degradation of pJAK1 via recruitment by suppressor of cytokine signaling 3 (SOCS3). This process, known as IL-2R signal desensitization, is antagonized in Tregs by the E3 ligase GRAIL (Gene Related to Anergy in Lymphocytes, RNF128), which mono-ubiquitinates Lys724 to block neddylation, preventing CRL5 activation and pJAK1 degradation. An imbalance between neddylation and mono-ubiquitination at Lys724 compromises IL-2R signaling and promotes autoimmune pathology, and studies show GRAIL expression is diminished in Tregs from autoimmune patients and mouse models, leading to reduced pSTAT5 activity and impaired suppressive capacity. Pharmacologic inhibition of neddylation with pathway inhibitors (NAEi) restores IL-2R signaling and Treg function, highlighting the therapeutic potential of targeting this regulatory axis to preserve immune tolerance.